EMPLOYABILITY OF YOUNG PEOPLE IN BRAZILIAN NORTHEAST: INFLUENCE FACTORS - Neves, Mateus de Carvalho Reis; Gonçalves, Marcos Falcão; de Lima, João Eustáquio (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
It was examined, in this study, how certain factors influenced the possibility of young people from 15 to 24 to entry into the labor market in the Brazilian Northeast. To this end, we analyzed the marginal effects of a logistic function applied to PNAD's – 2011 micro-data. The study revealed that education, work experience and age positively influenced integration into the labor market. Owning son, being female, non-white or living in urban areas has a negative relationship with the probability of working. These results suggest the path that may be followed by public policies aimed at alleviating unemployment among Brazilian Northeast young people.